KAMPANYE GEMA (GERAKAN BERSAMA) MELAWAN COVID-19 OLEH DINAS KESEHATAN KABUPATEN KARAWANG - Rulina Ega Armani; Siti Nursanti; Muhammad Ramdhani (Metacommunication: Journal of Communication Studies, 2021)
The purpose of this study is to plan the communication of the GEMA (Joint Movement) campaign against Covid-19 carried out by the Karawang District Health Office. The study used a qualitative method with a descriptive approach while the data interview techniques were interviews, direct interviews and literature studies. The results in this study show several stages that were passed in making communication planning for the campaign against Covid-19, namely data base line and needs assessment, determining communication objectives, planning analysis and strategy development, audience segmentation, media selection, message development, management planning, training, implementation and evaluation. The Joint Movement Campaign which was conducted from March to December 2020 took the form of 3M socialization. This campaign is focused on ages 18 to 50 using live media, social media and outdoor media. Evaluation of activities is carried out by looking at the graph of the distribution of Covid-19 cases in Karawang Regency. The obstacles that occur in this campaign are weather, vehicles and there are some people who still do not use masks properly..